2019
DOI: 10.1111/joor.12761
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a visual scoring method using gummy jelly for evaluating chewing efficiency in a large‐scale epidemiological survey

Abstract: Summary Background Several methods exist for objectively evaluating chewing efficiency by using gummy jelly. However, the validity of the subjective visual evaluation of chewing efficiency has not been assessed. Objective To verify with an epidemiological study, the validity of a visual scoring method using gummy jelly by testing the relationship between masticatory performance (MP) using a fully automatic measuring system and visual score (VS) using a visual scoring method. Methods Community‐dwelling elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Comparatively, the relative value of change in the masticatory performance (RVMP) is exactly the opposite of the masticatory performance value, the edentulous group demonstrated the highest improvement with a value of two times more than the pre-insertion Arare (bite-sized rice crackers) Gum Grilled meat Apple Each food item is classified according to its chewing index. 21 value, followed by the w/o PO group (21% increase), while the w/ PO group had the lowest improvement (17% increase). A significant difference was seen between the edentulous group and the w/PO group.…”
Section: The Objective and Subjective Assessmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Comparatively, the relative value of change in the masticatory performance (RVMP) is exactly the opposite of the masticatory performance value, the edentulous group demonstrated the highest improvement with a value of two times more than the pre-insertion Arare (bite-sized rice crackers) Gum Grilled meat Apple Each food item is classified according to its chewing index. 21 value, followed by the w/o PO group (21% increase), while the w/ PO group had the lowest improvement (17% increase). A significant difference was seen between the edentulous group and the w/PO group.…”
Section: The Objective and Subjective Assessmentsmentioning
confidence: 89%
“…Several methods such as sieving [17], color-changeable chewing gum [18] and gummy jelly [19] have been used for such assessments. Notably, masticatory performance assessment by using gummy jelly [19][20][21][22][23] was widely used as a diagnostic tool due to its fast, easy and accurate application, which is beneficial in a clinical setting. However, while objective assessments evaluate the actual masticatory function, it has been stressed that subjective evaluations are also appropriate and sensitive for measuring treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although no clear evaluation criterion exists for ICC values, following the evaluation criteria of Kappa coefficient used for similar purposes an ICC of 0.81 or higher is considered close to ideal . CV and ICC (2.1) of tongue pressure measurements used for diagnosing oral hypofunction were 0.091 and 0.653, respectively, and ICC (2.1) of masticatory function evaluation, which is also used to diagnose oral hypofunction, was 0.93, suggesting that the oral moisture‐checking device is as reliable as other evaluation methods. In this study, ICC (1.1) and ICC (2.1) of measured oral mucosa moisture values were very high in both the young and older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Validity and reliability of the visual scoring method have been reported, and this method is very easy to apply for evaluating shearing ability. A recent large‐scale cross‐sectional study reported that the difference between the shearing ability scores as calculated by the visual scoring method and glucose concentration method was slight; there was a significant correlation between these methods. However, in the visual scoring method, status of the gummy jelly being cracked or not crushed was evaluated as score 0; whereas the glucose concentration of these statuses was probably not the same.…”
Section: Discussionmentioning
confidence: 99%